Development of Leads to Social Inclusion Why do Similar Projects Have Different Outcomes? A Perspective on Local Government Actors - Terada, Taketo (Policy & Governance Review, 2025)
This study aimed to investigate the factors that contribute to social inclusion through urban redevelopment projects in metropolitan areas. Existing research argues that Japan's urban development system promotes redevelopment projects that prioritize corporate interests, while neglecting the interests of residents. Nevertheless, most redevelopment projects in Japan are led by local governments and their incentives are not limited to attracting corporate investment. Therefore, through case study analysis, this study examines how the involvement of local actors (bureaucrats) in redevelopment projects affects the degree of social inclusion. The hypothesis is that bureaucrat-led redevelopment, which is managed and led by the local administration with the master plan of the city, is likely to lead to social inclusion. The significance of this study is to expand the literature on the impact of gentrification policies on social inclusion by examining the case of Japan and providing suggestions for policymakers seeking sustainable urban development.